Hubungan Lama Demam dengan Hasil Pemeriksaan Antigen Nonstruktural 1 Dengue pada Pasien Demam Berdarah Dengue di RSUD Sultan Syarif Mohamad Alkadrie Tahun 2018 - Sari, Riski N.; Natalia, Diana; Parinding, Joni T. (Jurnal Biomedik : JBM, 2020)
Abstract: Mortality due to dengue hemorrhagic fever (DHF) in West Kalimantan is still quite high. One of the reasons of that is diagnostic delay. Nonstructural 1 antigen (NS1 Ag) test has been developed and can detect dengue virus infection since the onset of fever. This study was aimed to determine the relationship between duration of fever and NS1 Ag dengue in DHF patients at Sultan Syarif Mohamad Alkadrie Hospital in 2018. This was an observational and analytical study with a cross-sectional design. Samples were selected using a total sampling technique with a total sample of 34 patients. Data were obtained from medical records and were analyzed by using the independent T test with the Mann-Whitney test as an alternative test. Statistical analysis of the relationship between duration of fever and NS1 Ag obtained a p value of 0.000). In conclusion, there was a significant relationship between duration of fever and NS1 Ag in DHF patients at Sultan Syarif Mohamad Alkadrie Hospital in 2018.Keywords: dengue hemorrhagic fever (DHF), duration of fever, NS1 AntigenÂ Abstrak: Angka kematian akibat demam berdarah dengue (DBD) di Kalimantan Barat masih cukup tinggi; salah satu penyebabnya ialah keterlambatan diagnosis. Saat ini telah dikem-bangkan pemeriksaan antigen nonstruktural 1 (Ag NS1) yang dapat mendeteksi infeksi virus dengue sejak awal fase demam. Penelitian ini bertujuan untuk mengetahui hubungan lama demam dengan hasil pemeriksaan Ag NS1 dengue pada pasien DBD di RSUD Sultan Syarif Mohamad Alkadrie tahun 2018. Jenis penelitian ini ialah analitik observasional dengan desain potong-lintang. Sampel dipilih menggunakan teknik total sampling dan diperoleh jumlah sampel sebanyak 34 pasien. Pengumpulan data menggunakan rekam medis. Data dianalisis menggunakan uji T tidak berpasangan dengan uji alternatif Mann-Whitney. Hasil uji statistik terhadap hubungan antara lama demam dengan hasil pemeriksaan Ag NS1 mendapatkan nilai p=0,000. Simpulan penelitian ini ialah terdapat hubungan bermakna antara lama demam dengan Ag NS1 dengue pada pasien DBD di RSUD Sultan Syarif Mohamad Alkadrie tahun 2018.Kata kunci: demam berdarah dengue (DBD), lama demam, antigen NS1